The Heroes; Or, Greek Fairy Tales for My Children - Kingsley, Charles, 1819-1875 (Salt Lake City, UT : Project Gutenberg, 1996)
"The Heroes; Or, Greek Fairy Tales for My Children" by Charles Kingsley is a collection of retold Greek myths written during the late 19th century. The book serves as an engaging introduction to various legendary figures from Greek mythology, primarily aimed at children. The opening chapters focus on heroes like Perseus, providing not just thrilling tales but also moral lessons about bravery, wisdom, and the importance of doing good. The beginning of the stories features Perseus, who, after being cast away by his cruel grandfather, embarks on a heroic journey filled with challenges and adventures. Initially, we learn of the rivalry between the twin princes Acrisius and Proetus, which leads to the unjust treatment of Perseus' mother, Danae. The narrative delves into how Perseus vows to confront the terrifying Gorgon, Medusa, a promise he makes in a moment of anger. As Perseus prepares for his quest, he receives guidance from the goddess Athena, setting the stage for his transformation from a boy into a hero as he faces monstrous foes and fights for his rightful place. Overall, this enchanting beginning intertwines themes of heroism and moral growth, promising to capture the imaginations of young readers. (This is an automatically generated summary.)
Release date is 1996-10-01
Transcribed from the 1889 Macmillan and Co. edition by David Price
Keywords: Mythology, Greek -- Juvenile literature